Optimizing weight control in diabetes: antidiabetic drug selection - S Kalra (Dove Medical Press, 2010)
S Kalra1, B Kalra1, AG Unnikrishnan2, N Agrawal3, S Kumar41Bharti Hospital, Karnal; 2Amrita Institute of Medical Science, Kochi; 3Medical College, Gwalior; 4Excel Life Sciences, Noida, IndiaDate of preparation: 18th August 2010Conflict of interest: SK has received speaker fees from Novo Nordisk, sanofi-aventis, MSD, Eli Lilly, BMS, and AstraZeneca.Clinical question: Which antidiabetic drugs provide optimal weight control in patients with type 2 diabetes?Results: Metformin reduces weight gain, and may cause weight loss, when given alone or in combination with other drugs. Pioglitazone and rosiglitazone use is associated with weight gain. Use of the glucagon-like peptide-1 (GLP-1) analogs, liraglutide and exenatide, is associated with weight loss. Dipeptidyl peptidase-4 (DPP-4) inhibitors are considered weight-neutral. Results with insulin therapy are conflicting. Insulin detemir provides weight control along with glycemic control.Implementation: • Weight gain is considered an inevitable part of good glycemic control using conventional modalities of treatment such as sulfonylureas.• Use of metformin, weight-sparing insulin analogs such as insulin detemir, and liraglutide, should be encouraged as monotherapy, or in combination with other drugs.Keywords: weight control, diabetes